Analisis Yuridis Terhadap Perjanjian Sewa Menyewa Yang Dilaksanakan Antara Suami Isteri Yang Berbeda Kewarganegaraan Di Indonesia (Studi Putusan Makamah Agung Nomor 3403 K/Pdt/2016) - Jesslyn Gozali (Universitas Islam Sumatera Utara, 2021)
The Article 1548 of the Civil Code explains that a lease is an agreement, whereby one party binds himself to give the other party the enjoyment of an item, for a certain period of time and with the payment of a price which the party has agreed to pay later. The limitation regarding the rental period are not set but based on the agreed period as well as the parties it is not explicitly explained whether a husband and wife can do a lease agreement. The prohibition imposed on married couples is only a legal act of buying and selling contained in the Article 1467 of the Civil Code. In practice in the field, there is a land lease agreement made in the form of an Authentic Deed with the parties at the time of making the lease agreement the land is still a husband and wife with different nationalities has been terminated and declared proven to have committed legal smuggling to control land in Indonesia on the basis of property rights by The Supreme Court in its decision Number 3403 K/Pdt/2016. The problem that can be raised in this study is whether a land lease agreement can be made by a married couple of different nationalities with the object of the agreement coming from joint property? If it is related to the authority to act on the parties in the lease agreement with the object coming from joint property and the principle of propriety as well as the judge's consideration in deciding the cases of land lease agreements between husband and wife of different nationalities which only refers to the characteristics of the lease term and the reasons that are not halal but not with the status of the parties at the time of making the lease agreement in the decision of the Supreme Court Number 3403 K/Pdt/2016.The results of the research indicate that the land lease agreement between husband and wife of different nationalities with the object of the lease agreement coming from joint property without performed the separation of assets is inappropriate and contrary to the propriety principle of Article 1339 of the Civil Code and the authority to act and the basis for the judge's consideration in canceling the lease agreement must consider the status of the legal relationship between the AMP (foreigner) and KP (WNI) and the object of the agreement, not only focusing on illegal causes and the time period considered by the judge contradicts the characteristics the characteristics of lease rights which have a limited period of time but in essence the time limit is not determined but the time limit is based on a mutual agreement between the parties.Keywords : Lease Agreement, Husband and Wife, Propriety Principle